Peranan Krusial Penyidik Pegawai Negeri Sipil dalam Penegakan Hukum Pidana Lingkungan Berdasarkan Undang-Undang Nomor 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Amini Nst, Aisyah Putri; Senjaya, Murshal (Wajah Hukum, 2025)
This study examines the critical role of Civil Servant Investigators (PPNS) in enforcing environmental criminal law under Law Number 32 of 2009 on Environmental Protection and Management. PPNS holds strategic authority in investigating environmental crimes, such as hazardous waste pollution and ecosystem destruction, yet faces challenges including limited resources, corporate resistance, and suboptimal inter-agency coordination. Employing a normative juridical approach with statutory and case analysis, this research evaluates the effectiveness of PPNS’s role and its collaboration with the police. Findings indicate that enhancing PPNS capacity through training, technological facilities, and regulatory reforms, including broader adoption of the strict liability principle, can improve environmental law enforcement. The study recommends establishing integrated coordination protocols and joint task forces to support environmental sustainability in Indonesia.